Numerical test study on propagation law of cylindrical wave superimposed into plane wave and response characteristics of rockbolts - Ziyou YANG; Benshui YANG; Yang HE; Junjie LIU (Meitan xuebao)
In order to reproduce the visualization process and propagation laws of plane waves formed by the superposition of explosive cylindrical waves, with reference to the results of the indoor model test as a reference basis, a numerical test was carried out to investigate the interaction between the superposition of explosive cylindrical waves and the surrounding rock of the anchorage cavern with the help of nonlinear explicit dynamic analysis software. The propagation law of plane wave in the rock mass was analyzed, the distribution characteristics of dynamic cracks in the surrounding rock of unreinforced and anchorage caverns were compared, and the response laws of the rockbolts to the plane wave were discussed and analyzed in comparison with the results of the corresponding model tests. The results showed that the cylindrical waves formed after the explosion of the cylindrical charge by superimposing on each other were able to form plane waves above and below the charge plane and were reflected to produce tensile waves when they propagated to the upper surface of the model and to the vault of the caverns, and tensile cracks were produced in both places. The cracks distribution patterns near the surrounding rock of the unreinforced cavern anchorage cavern were basically the same, except that the width of crack distribution at the arch foot of unreinforced cavern was slightly larger than that of the reinforced cavern. The strain peak in the middle of the anchor rod was larger than that of its ends and roots, and the overall deformation is mainly in tension, which was consistent with the roles of the rockbolts in improving the tensile strength of the surrounding rock. The rockbolts’ end was less constrained by the surrounding rock resulting in a tension-compression ratio of approximately 3.2 times that of the root. The simulated axial strain waveform curves of the rockbolts were compared with the corresponding curves of the model tests’, and it was found that both of them had better consistency in the trend of change, and the lengths of the measured axial strain waveform curves of the compression and tensile segments were about twice as long as those of their corresponding simulated waveform curves, and the peak values of the measured axial strain were also larger than those of their corresponding simulation. It is known that plane waves can be formed by superposition of cylindrical waves to obtain the plane wave loads required to carry out model tests and numerical tests.